2019
DOI: 10.1002/mpr.1802
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent short forms of the Situational Feature Recognition Test 2: Psychometric properties and analysis of interform equivalence and test–retest reliability

Abstract: ObjectiveTo obtain two equivalent short forms of the “Situational Feature Recognition Test, Version 2,” a social perception test, and their psychometric properties.MethodsPatients with schizophrenia (n = 101) were assessed at two different times. Statistical analyses were performed as follows: (1) Cronbach's alpha was used to assess reliability; (2) Spearman correlations, Wilcoxon signed‐rank test, and a 2 (form) × 2 (time) repeated measures multivariate analysis of variance were used to analyse interform equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…The higher the reliability, the more we can trust that the measurement scale score is an accurate reflection of actual individual differences (Hayes & Coutts, 2020). The reliability is measured through an analysis of test‐retest, split‐half reliability, congeneric estimates and internal consistency (Gómez‐Gastiasoro et al ., 2019; Siddi et al ., 2018). These estimates are estimated using coefficients such as MS, LCRC, lambda‐2, McDonald’s Omega, Cronbach's alpha and Spearman correlations coefficient (Bakolis et al ., 2019; Hayes & Coutts, 2020; Riou et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The higher the reliability, the more we can trust that the measurement scale score is an accurate reflection of actual individual differences (Hayes & Coutts, 2020). The reliability is measured through an analysis of test‐retest, split‐half reliability, congeneric estimates and internal consistency (Gómez‐Gastiasoro et al ., 2019; Siddi et al ., 2018). These estimates are estimated using coefficients such as MS, LCRC, lambda‐2, McDonald’s Omega, Cronbach's alpha and Spearman correlations coefficient (Bakolis et al ., 2019; Hayes & Coutts, 2020; Riou et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For construct validity, convergent and discriminant validity were assessed. Some papers described the assessment of convergent validity by comparing constructs that were theoretically similar to determine their inter-correlations (Eklund et al , 2018; Eline et al , 2014; Gómez‐Gastiasoro et al , 2019). For instance, Eklund et al (2018) reported in a study that quality of life and self-mastery constructs were theoretically similar to self-esteem and so could be suitable to assess convergent validity.…”
Section: Analysing Measurement Models Of Consumer Instrumentmentioning
confidence: 99%
“…For instance, Eklund et al (2018) reported in a study that quality of life and self-mastery constructs were theoretically similar to self-esteem and so could be suitable to assess convergent validity. The discriminant validity is also assessed by comparing constructs that are theoretically different and thus show low or no correlation (Eline et al , 2014; Gómez‐Gastiasoro et al , 2019). Specifically, discriminant validity was used to determine whether constructs that were not in the same model were truly distinct (Riou et al , 2016).…”
Section: Analysing Measurement Models Of Consumer Instrumentmentioning
confidence: 99%
See 2 more Smart Citations